2003
DOI: 10.1111/j.1553-2712.2003.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Total Out-of-hospital Time a Significant Predictor of Trauma Patient Mortality?

Abstract: Provider-assigned CUPS status, patient age, Injury Severity Score, and Revised Trauma Score all were significant predictors of trauma patient mortality. Total out-of-hospital time was not associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 14 publications
4
44
0
1
Order By: Relevance
“…The time factor would appear to be subordinate in terms of pre-hospital treatment of severe trauma patients. This finding is in accordance with Lerner's study, which found that after correction for ISS, patient characteristics and treatment aspects, there was no relation between the time from the moment of the accident to the patient's arrival at hospital on the one hand and the risk of death on the other [25]. The conclusions of Lerner's study and our own should, however, be interpreted with some caution.…”
Section: Discussionsupporting
confidence: 91%
“…The time factor would appear to be subordinate in terms of pre-hospital treatment of severe trauma patients. This finding is in accordance with Lerner's study, which found that after correction for ISS, patient characteristics and treatment aspects, there was no relation between the time from the moment of the accident to the patient's arrival at hospital on the one hand and the risk of death on the other [25]. The conclusions of Lerner's study and our own should, however, be interpreted with some caution.…”
Section: Discussionsupporting
confidence: 91%
“…Time to treatment is presumed to be a significant factor in trauma outcomes, 41 and would disparately impact rural populations, 5,6 but evidence for the relationship between pre-hospital time and mortality is widely variable. 30,32,[42][43][44][45][46][47][48][49][50][51][52] Other factors, such as community-level wealth and insurance coverage, [53][54][55] may also contribute to geographic disparities in injury mortality. Further research is needed to examine the potentially complex network of factors that determine injury outcomes for rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the possibility of early therapy may be related to the common concept in many trauma centers referred as the "golden hour," suggesting that very early interventions are critical to save lives after injury (71). This concept has been challenged by several clinical studies (72)(73)(74). However, the information gathered from our studies, as well as the capacity to predict mortality very early after CLP, may pose an experimental model to test the hypothesis that initial interventions during the "golden hour(s)" may improve survival in trauma and critically ill patients.…”
Section: Discussionmentioning
confidence: 99%